Sosialisasi Pedagodik TPACK Untuk Guru: Meningkatkan Kualitas Pembelajaran di Era Digital - Fine Eirene Siahaan; Sanggam Siahaan; Siska Anggita Situmeang; Novra Melisa P. Hutabarat; Basar Lolo Siahaan; Irene Adryani Nababan; Rio parsaoran Napitupulu; Bernard Simanjuntak (Jurnal Medika: Medika, 2025)
The development of digital technology requires teachers to be able to integrate technological, pedagogical, and content knowledge (TPACK) into the learning process. However, many teachers still struggle to understand and apply TPACK optimally, resulting in suboptimal learning quality in the digital era. This community service activity aims to improve teachers' understanding and skills in implementing TPACK through socialization and structured training. The methods used include lectures, discussions, hands-on practice in developing TPACK-based lesson plans, as well as pretest and posttest evaluations. The activity was conducted at SMP Negeri 11 Pematangsiantar in March-April 2025, involving teachers as active participants. Evaluation results showed a significant improvement in teachers' understanding of TPACK concepts and practices, reflected in an average increase in pretest scores from 27.9% to 57.37% on the posttest. Teachers also became more confident in designing technology-based learning and effectively utilizing digital media. This activity demonstrated that TPACK socialization can strengthen teachers' competencies and improve the quality of learning in the digital age. Continuous support and further training are still needed to ensure optimal implementation of TPACK.